Perception Analysis of Visitors on Placemaking at Pasar Kreatif dan Seni Lampung as a Communal Space - Hafizhah Salwa Balqis; Agung Cahyo Nugroho (Universitas Bandar Lampung (UBL), 2026)
Pasar Kreatif dan Seni Lampung (PAKSI) is a public space with the potential to be a place for social interaction, art activity, and community activity in Lampung Province. However, the low levels of visitation, activity intensity, space utilization, and community participation led to in its function being suboptimal. This study aims to analyze visitors’ perceptions of the placemaking concept application in the area, based on the four elements of the Project for Public Spaces, namely access and linkages, comfort and images, uses and activities, and sociability. This research also relates these elements to the creative placemaking approach that emphasizes art, culture, and community engagement. The method used is a mixed methods which includes 50 respondents who have visited this area. The result show that majority of respondents have a positive perception of spatial comfort and the potential for social interaction. However, aspects of accessibility, activities contuinity, and promotion are still considered suboptimal. This indicates that to develop PAKSI as a sustainable communal space, efforts are needed to strengthen uses perception based on placemaking elements, combined with creative placemaking strategies to build local indentity and enchance community attachment to the space.